Role of diffusion: weighted magnetic resonance imaging in evaluation of renal masses - Meena, Jitendra K.; Taneja, Anil (International Journal of Research in Medical Sciences, 2020)
Background: Diffusion-weighted magnetic resonance imaging (DWI) is a valuable tool to narrow down the differential diagnosis of renal masses. Studies have shown that benign renal masses have higher Apparent diffusion coefficient (ADC) value than malignant renal masses. Aim of study was to evaluate the role of diffusion-weighted magnetic resonance imaging in the characterization of renal masses. Methods: The study was conducted in department of Radio diagnosis at ABVIMS and Dr. RML Hospital, New Delhi between June 2017 to March 2019. This was a cross-sectional observational study comprising of 28 patients. Patients found to have renal mass on ultrasound and computed tomography (CT) were evaluated further on 3T siemens Magnetic resonance imaging (MRI) scanner. In addition to routine sequences, DWI using b value of 0,500,1000 s/mm2 sequence was used to study to differentiate benign and malignant renal masses. Results: Of a total of 28 cases, the most common malignant mass was renal cell carcinoma (RCC). Angiomyolipoma (AML) was the most common benign masses. DWI showed low ADC values in most of the malignant masses and high ADC values in most of the benign masses. The cut-off level of ADC value for differentiation among benign and malignant renal masses was 1.08×10-3 mm2/s. DWI-MR findings were correlated with histopathological diagnosis. Conclusion: DWI with ADC measurements are a non-invasive, problem solving tool for characterization of renal masses helping to differentiate malignant from benign masses.